On the performance of a hollow-fiber bioreactor for acidolysis catalyzed by immobilized lipase - Balcão, Victor M. (2011)
The present communication describes the chemical modification of anhydrous butterfat by interesterification with oleic acid catalyzed by a lipase of Mucor javanicus. Two reactor configurations were tested, a batch-stirred tank reactor containing suspended lipase and a batch-stirred tank reactor in combination with a hollow-fiber membrane module containing adsorbed lipase. The goal of this research was to assess the advantage of using a (hydrophobic) porous support to immobilize the lipase in attempts to engineer butterfat with increased levels of unsaturated fatty acid residues (oleic acid) at the expense of medium-to-long chain saturated fatty acids (myristic and palmitic acids). Reactions were carried out at 40°C in the absence of solvent under controlled water activity, and were monitored by chromatographic assays for free fatty acids. The results obtained indicate that the rate of interesterification using the proposed reactor configuration is enhanced by a factor above 100 relative to that using suspended lipase, for the same protein mass basis. Although hydrolysis of butterfat occurred to some degree, the enzymatic process that uses the hollow-fiber reactor was technically superior to the stirred tank system.